A new method for broadening the detection range of immunoassay and its application in β-hCG quantitative detection. Issue 15 (29th March 2022) - Zhang, Bei; Guo, Miao; Zhang, Tianjie; Liu, Dandan; Tan, Xin; Li, Xue; Yu, Yang; Li, Huiqiang
Abstract : The combination of two solid-phase monoclonal antibodies with different affinities allows the antibodies to act selectively according to the concentration of β-hCG in the sample, thus ensuring sensitivity and broadening the detection range. Abstract : Early pregnancy prediction requires very high β-hCG detection sensitivity, while embryonic development monitoring and trophoblastic disease detection require a wider detection range. In this study, based on light-initiated chemiluminescence assay (LICA), one high-affinity mAb and one low-affinity mAb were selected and coated on chemibeads with a larger coating area in different ratios to immobilize the antibodies. The two immobilized mAbs were mixed with different concentrations to detect β-hCG. When the high-affinity mAb-coated chemibeads and low-affinity mAb-coated chemibeads were used at working concentrations of 0.100 mg mL −1 and 0.014 mg mL −1, respectively, the sensitivity and detection range were maximized. The assay was precise for measuring β-hCG with repeatability and intermediate precision of <5% CV. The assay has a high sensitivity with a limit of quantification (LoQ) of 0.49 IU L −1, which is lower than that of most β-hCG detection kits. Over the range of 1 IU L −1 to 16 000 IU L −1, the assay had a proper linearity ( r = 0.9995). No false negative results due to the hook effect were observed at β-hCG concentrations up to 225 000 IU L −1 . The assay showed a good correlation with the Abbott assay ( r = 0.9910). LICA combined with immobilized mAbs with different affinities ensures the sensitivity of β-hCG detection and broadens the detection range.